Typology of alcohol consumers in five Australian nighttime entertainment districts. (14th December 2015) - Peacock, Amy; Norman, Thomas; Bruno, Raimondo; Pennay, Amy; Droste, Nicolas; Jenkinson, Rebecca; Quinn, Brendan; Lubman, Dan I.; Miller, Peter
Abstract: Introduction and Aims: Understanding how types of alcohol consumers differ is important for public policy targeted at reducing adverse events. The aims of the present study were to identify typologies of alcohol consumers in Australian nighttime entertainment districts based on risk factors for harm and to examine variation between the identified groups in drinking setting and harms. Design and Methods: Street‐intercept surveys were conducted with 5556 alcohol consumers in and around licensed venues in five Australian cities between November 2011 and June 2012. Latent class analysis identified groups based on age and sex, and blood alcohol concentration, pre‐drinking, energy drink use and illicit drug use during that night. Results: Four classes were identified: general patron group (33%), young pre‐drinker group (27%), intoxicated male pre‐drinker group (31%) and intoxicated illicit drug male group (9%). The proportion of the general patron group interviewed decreased over the night, while the other groups increased (particularly in regional cities). As compared with the general patron group, the remaining three groups reported increased odds of being involved in aggression and any alcohol‐related injuries in the past 3 months, with highest rates of harm amongst the intoxicated illicit drug male group. Discussion and Conclusions: Alcohol consumers in nighttime entertainment districts are not a homogeneous group. One‐third have a low likelihood of risky consumption practices; however, representation of this consumer class diminishes throughout the night. Elevated harms amongst groups characterised by certain risk factors (e.g. pre‐drinking and illicit drug use) emphasise the importance of addressing these behaviours in public policy. [Peacock A, Norman T, Bruno B, Pennay, Droste N, Jenkinson R, Quinn B, Lubman DI, Miller P. Typology of alcohol consumers in five Australian nighttime entertainment districts. Drug Alcohol Rev 2016;35:539–548]